2015
DOI: 10.1002/2015gl063624
|View full text |Cite
|
Sign up to set email alerts
|

Determining the source characteristics of explosions near the Earth's surface

Abstract: We present a method to determine source characteristics of explosions near the Earth's surface. The technique accounts for the reduction in amplitudes as the explosion depth approaches the free surface and less energy is coupled into the ground. We apply the method to the Humming Roadrunner series of shallow explosions in New Mexico where the yields and depths are known. Knowledge of the material properties is needed for both source coupling/excitation and the free surface effect. Although there is the expecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…Various methods, such as the spectral ratio analysis method (Murphy et al, 2010(Murphy et al, , 2013, hydrodynamic calculation method (Rougier et al, 2011) and regional waveform envelope method (Pasyanos & Ford, 2015;Pasyanos & Myers, 2018;Pasyanos et al, 2012), have been explored by different authors to determine the burial depth of an underground nuclear test. Interferometric synthetic aperture radar (InSAR) surface displacement data obtained at the NKTS could also constrain the burial depths, epicenters and yields of these six events (Wei, 2017;Myers et al, 2018;Sreejith et al, 2020;Wang et al, 2018).…”
mentioning
confidence: 99%
“…Various methods, such as the spectral ratio analysis method (Murphy et al, 2010(Murphy et al, , 2013, hydrodynamic calculation method (Rougier et al, 2011) and regional waveform envelope method (Pasyanos & Ford, 2015;Pasyanos & Myers, 2018;Pasyanos et al, 2012), have been explored by different authors to determine the burial depth of an underground nuclear test. Interferometric synthetic aperture radar (InSAR) surface displacement data obtained at the NKTS could also constrain the burial depths, epicenters and yields of these six events (Wei, 2017;Myers et al, 2018;Sreejith et al, 2020;Wang et al, 2018).…”
mentioning
confidence: 99%
“…The framework discussed here is straightforwardly extensible. Other acoustic features related to the negative phase (Schnurr et al, 2020) could be included, and other seismic features such as the coda (Pasyanos & Ford, 2015;Yoo, 2017) and surface waves (Bonner et al, 2013a;Napoli & Russell, 2018) could be incorporated to infer explosive yield at regional distance. The framework could be improved by testing the chemical-nuclear equivalence assumptions for near-surface events.…”
Section: Discussionmentioning
confidence: 99%
“…Our approach using a physics‐based propagation model can be extended to seismoacoustic yield estimation. Pasyanos and Ford (2015) demonstrated that joint seismic and acoustic likelihoods can substantially improve the determination of yield and depth‐of‐burial (DOB). Although our inversion was performed for a surface explosion based on K21, we can explore how different yields and depths can produce similar acoustic amplitudes based on the seismoacoustic energy partitioning (Ford et al., 2014; Pasyanos & Kim, 2019) (Text S2 in Supporting Information ).…”
Section: Acoustic Methodsmentioning
confidence: 99%